Building a Science Diplomacy Curriculum - Mauduit, Jean-Christophe; Gual Soler, Marga (Frontiers in Education, 2020)
Science diplomacy is a fast-growing field of research, education and practice dedicated to better understanding and reinforcing the connections between science, technology and international affairs, in order to tackle national and global challenges. Interest from early-career scientists and young diplomats to learn more and engage at the science-diplomacy nexus is growing all around the world. However, as a relatively new and multidisciplinary field, we show that science diplomacy has so far been largely taught through extracurricular courses and workshops, often self-organized by university student groups or international scientific organizations, targeting specific disciplinary and geographic audiences. Given this fragmented landscape, we map and categorize current science diplomacy educational offerings in higher education. Despite some coverage of science diplomacy within general science policy programs or courses focused on an issue area (e.g. water diplomacy or environmental diplomacy), a structured foundational course addressing the commonalities of all the scientific and technological issues relevant to international affairs is still lacking. Hence, we first suggest knowledge and key skills scientists and diplomats can learn from each other to bridge the disciplinary divide and engage in science diplomacy scholarship and practice. Building upon it, we then propose cross-cutting, core concepts that can inform the establishment and consolidation of science diplomacy curricula at universities. These aim to be useful to teach science diplomacy to advanced undergraduate and graduate students of all backgrounds and to be adaptable to a wide range of degree programs and disciplines.